2017
DOI: 10.2134/itsrj2016.05.0366
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wear and Soil Compaction on Kentucky Bluegrass Sod Rooting and Plant Recovery

Abstract: Damage areas in sport fields from wear are often sodded before complete rooting. The objective of this study was to examine the influence of traffic (the combined effects of wear and soil compaction) on sod rooting. Poa pratensis L. sod was installed in September 2008 and 2009 on a silt loam and a sand rootzone at the University of Massachusetts‐Amherst. Treatments included a compaction and noncompaction soil and wear and nonwear treatments, which were evaluated under the influence of two soils. Compaction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…This is consistent with other reports of more severe injury and slower recovery on turf plots treated with abrasive wear compared to cleated traffic. Research showed wear stress being more detrimental than compaction of the soil to turf performance (Cashel et al., 2005; Dest & Ebdon, 2017; Dest et al., 2009; Park et al., 2016). As a result, abrasive wear appeared to be more efficient at identifying wear tolerant (greater differences in FTC among fine fescues) than cleated traffic.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other reports of more severe injury and slower recovery on turf plots treated with abrasive wear compared to cleated traffic. Research showed wear stress being more detrimental than compaction of the soil to turf performance (Cashel et al., 2005; Dest & Ebdon, 2017; Dest et al., 2009; Park et al., 2016). As a result, abrasive wear appeared to be more efficient at identifying wear tolerant (greater differences in FTC among fine fescues) than cleated traffic.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17]. 본 연구는 내환경성이 우수하여 운동장에 사용하기 에 적합하다 여겨지는 들잔디 '제니스'의 답압에 의한 마모 스트레스를 기존의 형태적, 생리적 분석과 더불어 RGB 이미 지 분석을 통한 잔디 생육 특성을 보다 정량적이며 객관적으 로 평가하기 위해 수행하였다.…”
unclassified